IMF Survey, Volume 35, Issue 11. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
Multilateral consultation; Euro Area; Caruana to head new Department; Marshall Islands; Malaysia; Inflation targeting; Offshoring U.S. services; Public sector credit; Singapore; Pakistan's inflation; Kyrgyz Republic; Latin America.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet